2019
DOI: 10.1111/ajt.15126
|View full text |Cite
|
Sign up to set email alerts
|

Better graft outcomes from offspring donor kidneys among living donor kidney transplant recipients in the United States

Abstract: A recent study reported that kidney transplant recipients of offspring living donors had higher graft loss and mortality. This seemed counterintuitive, given the excellent HLA matching and younger age of offspring donors; we were concerned about residual confounding and other study design issues. We used SRTR data 2001–2016 to evaluate death-censored graft failure (DCGF) and mortality for recipients of offspring versus non-offspring living donor kidneys, using Cox regression models with interaction terms. Reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…We read with great interest the report "Better graft outcomes from offspring donor kidneys among living donor kidney transplant recipients in the United States." 1 The conclusions of Holscher et al differ considerably from those in our recent paper "Inferior longterm allograft and patient outcomes among recipients of offspring living donor kidneys," 2 and we appreciate the opportunity to respond to their criticisms of our work.…”
Section: Identifying the Best Donor For The Best Recipient: Parents Mmentioning
confidence: 75%
“…We read with great interest the report "Better graft outcomes from offspring donor kidneys among living donor kidney transplant recipients in the United States." 1 The conclusions of Holscher et al differ considerably from those in our recent paper "Inferior longterm allograft and patient outcomes among recipients of offspring living donor kidneys," 2 and we appreciate the opportunity to respond to their criticisms of our work.…”
Section: Identifying the Best Donor For The Best Recipient: Parents Mmentioning
confidence: 75%
“…[25][26][27] One recent study of living-related-donor kidney transplants showed that close HLA matching between child donors and parent recipients afforded lower rates of graft failure and comparable mortality. 28 The OPTN VCA data do not report information on the HLA mismatch among living-donor uterus transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies explore the influence of HLA mismatch in living‐donor SOT outcomes, with varying results reported in the liver literature, when examining analyses of OPTN vs international data 25–27 . One recent study of living‐related‐donor kidney transplants showed that close HLA matching between child donors and parent recipients afforded lower rates of graft failure and comparable mortality 28 . The OPTN VCA data do not report information on the HLA mismatch among living‐donor uterus transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…We appreciate the thoughtful letter from Cohen et al regarding our recent papers on outcomes following kidney transplant from an offspring donor. 1 It is only after the provision of individualized estimates of short-and long-term risks associated with kidney donation that recipient outcomes should be considered. We suggest that potential donors be compared using a metric scaled for meaningful interpretation, such as the living kidney donor profile index (LKDPI), www.transplantmodels.com/lkdpi.…”
Section: Offspring Living Kidney Donors Should Not Be Ruled Outmentioning
confidence: 99%